A Comparative Study of the Concept of Adultery Offenders in At-Tasyri’ Al-Jina’i Al-Islami and the Aceh Qanun Number 6 of 2014 on Jinayat Law - Andi Muhammad Firdaus Tamin; Syahruddin Nawi; Hardianto Djanggih; Anzar Makkuasa (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study aims to analyze and compare the concept of zina offenders in At-Tasyri’ Al-Jina’i Al-Islami by Abdul Qadir Audah with the provisions stipulated in Aceh Qanun Number 6 of 2014 concerning Jinayat Law. This study is important to understand how the concepts of classical Islamic criminal law found in the literature of fiqh jinayah are adopted and adapted within the regional positive legal system in Aceh, which has special authority in implementing Islamic law. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. The legal materials consist of primary legal sources, namely At-Tasyri’ Al-Jina’i Al-Islami and Aceh Qanun Number 6 of 2014, as well as secondary legal materials in the form of books, scientific journals, and relevant previous studies. The analysis is conducted using a descriptive-comparative method to identify similarities and differences in the legal concepts contained in the two sources. The results show that both share similarities in their theological foundation, objectives of punishment, and the principle of caution in proving the offense of zina through confession and the testimony of four witnesses. However, fundamental differences exist in the definition of zina, the classification of offenders, and the types of sanctions imposed. At-Tasyri’ Al-Jina’i Al-Islami distinguishes offenders between muhsan and ghairu muhsan with sanctions of stoning and flogging, whereas the Aceh Qanun simplifies the classification of offenders and only imposes flogging as the principal punishment. These differences indicate a process of adaptation and positivization of Islamic law within the Indonesian national legal system by considering aspects of public welfare, the effectiveness of law enforcement, and human rights principles